Impacts Seed Technology Improvement on Economic Aspects of Chilli Production in Central Java - Indonesia - Mariyono, Joko (Universitas Muhammdaiyah Surakarta, 2016)
Vegetable production, including that of chillies, plays an important role in agricultural sector and rural economic development worldwide. This is because of greater farm productivity with regard to vegetables than cereal and staple crops. This paper analyses the impact of seed technology development on the economic aspects of chilli production in Central Java. Particular attention is paid to improved varieties of chilli. Potential consequences of seed technology development are discussed. Data of this study are compiled from surveys conducted in three selected chilli producing regions in 2010-2012. The results show that the major varieties of chilli grown by surveyed farmers are grouped into three broad types: hybrids, local and improved open pollinated varieties. The chilli varieties farmers selected varied according to location and cropping season. In the dry season, farmers grew similar proportions of hybrid, local, and open pollinated types. Nevertheless, there were differences among the survey sites. Farmers grew different varieties to exploit seasonal microclimates and market preferences. Mostly, farmers selected varieties for economic motives. The consequence of growing hybrids was less use of agrochemicals, particularly pesticides, than for other varieties. Overall, they show the best economic performance in the study site. Development of seed technology should consider agro-ecological and economic aspects to obtain better outcomes. Private sector and national research institutions need to collaborate more to utilise available genetic resources to produce better varieties of chilli.